The attitude of Egyptian Nubian university students towards Arabic and Nubian languages - Abou-Ras, Sanaa Gamal (AUC Knowledge Fountain, 2012)
This research investigates the attitude of Egyptian Nubian university students towards the Arabic and the two Nubian languages, Nobiin and Kenuzi-Dongola. The Nubian languages are called by Egyptian Nubians, Fadijja/Fadicca and Kenzi, respectively. Nubians are people who live in the Nubia area which lies between Egypt's southern borders with the northern part of Sudan. Nubia is divided into two parts - one under the Egyptian regime, and the other under the Sudanese regime. The number of participants used in the study was forty - half male and half female. Twenty of these participants live in the Nubian region and are enrolled at the South Valley University in Aswan, Egypt. This number was compared with an additional twenty Egyptian-Nubian university students who live outside the Nubian region and attend various Egyptian universities located in Alexandria and Cairo. The hypothesis of this study is that Egyptian Nubian university students tend to have positive attitudes toward Arabic and also the Nubian languages. This research is a qualitative and partially quantitative one. Observations, questionnaires, and interviews were used to collect data in order to explore the following: (1) the language students prefer to speak at home and in public and if language preferences are gender-related, (2) the factors that influence the Egyptian Nubian university students' attitudes towards Arabic and Nubian languages, and (3) a look at the future of these ethnic Nubian languages. Results that answered the main question on the attitude of Egyptian Nubian university students toward Arabic and Nubian languages revealed that students who live inside and outside the Nubian region tend to have positive attitudes towards both the Arabic and the Nubian languages.